The Establishment and Use of Text Corpora at Birmingham University - Renouf, Antoinette (HERMES - Journal of Language and Communication in Business, 1991)
The School of English at Birmingham University has over the last ten years increasingly integrated the study and use of corpora into its research and teaching activities. Cobuild Ltd and the English for Overseas Students Unit are particularly active, as is the Research and Development Unit for English Language Studies. Members of the Research Unit have created the purpose-built corpora that make up the Birmingham Collection of English Text. The Research Unit is using these to support its linguistic research projects and the development of new types of text-processing software, as well as for specialised teaching purposes.